Kindergarten Registration Management System (KREMS) - Ibrahim, Amirah; Mohamed, Hasiah (SOTVI, 2019)
Â Kindergarten Registration Management System (KReMS) is a systemthat has been developed for one of the kindergarten in Dungun. Thissystem is proposed to be developed in order to help the management ofthe kindergarten to manage the registration process. The user for thissystem can be divided into four which are parent, admin, staff andteacher. KReMS basically have eight modules which are studentregistration, fees payment, generating report, announcement to parent,updating vacancies in the kindergarten, upload receipt and importantdocuments, update status, and record parent, staff and studentinformation. The methodology used to develop KReMS is RapidApplication Development (RAD). KReMS is evaluated by experts andusers. The evaluation of KReMS is done with four experts based on fivecriteria which are flow of the system, interface, efficiency, ease of use,and user experience. From this evaluation, the result shows that most ofthe experts agree that KReMS the interface of KReMS is attractive.Apart from that, userâ€™s evaluation that involved 30 respondents has beenconducted. Questionnaire is distributed to the respondents and therespondents evaluated the system based on six constructs which areinterface, usability, efficiency, satisfaction, ease of use and userexperience. Result shows that most of the respondents agreed that thesystem will be able to improve the efficiency of their works with thehighest mean which is 4.36 (SD= 0.62). As for the future enhancement,one of features that can be added is ability of the system to recordstudent attendance